2004
DOI: 10.4088/jcp.v65n1014
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Birth in Seasonal Affective Disorder

Abstract: Background: Seasonal affective disorder (SAD) is defined as a form of recurrent depressive or bipolar affective disorder characterized by recurrent affective episodes, that occur annually at the same time of the year (Rosenthal et al., 1984). Season of birth is a putative etiological factor for several psychiatric illnesses. An excess of late

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…Surprisingly, only one published study has examined possible season-of-birth effects in SAD. In a large European study, Pjrek et al (2004) found an excess of spring-summer births in SAD patients compared to the general population. A highly novel finding, which has particular relevance to our own work, is that different season-of-birth effects were found depending on vegetative symptoms.…”
Section: Season-of-birth Effectsmentioning
confidence: 95%
“…Surprisingly, only one published study has examined possible season-of-birth effects in SAD. In a large European study, Pjrek et al (2004) found an excess of spring-summer births in SAD patients compared to the general population. A highly novel finding, which has particular relevance to our own work, is that different season-of-birth effects were found depending on vegetative symptoms.…”
Section: Season-of-birth Effectsmentioning
confidence: 95%
“…More specifically, an association between the short allele of the serotonin transporter gene and atypical symptoms [67], and between the 7-repeat variant of the Dopamine-4 Receptor gene and obesity [68], have been found in SAD patients. Season of birth effects may also play a role in this regard [69,70]. Although similar hypotheses in DSM-defined atypical depression have not been tested to date, these data in SAD point to a role for both specific genes and unknown factors tied to birth season in shaping atypical symptomatology.…”
Section: The Pathophysiology Of Atypical De-pressionmentioning
confidence: 91%
“…Several psychiatric studies mentioned a higher frequency of winter and spring birth date for patients with schizophrenia and of spring and summer birth date for patients with affective disorders [9,10]. However, this data has not always been confirmed [11].…”
Section: Introductionmentioning
confidence: 95%